Reductive dissolution of iron phosphate modifies rice root morphology in phosphorus-deficient paddy soils. (February 2023) - Wang, Chaoqun; Thielemann, Lukas; Dippold, Michaela A.; Guggenberger, Georg; Kuzyakov, Yakov; Banfield, Callum C.; Ge, Tida; Guenther, Stephanie; Dorodnikov, Maxim
Abstract: Root morphology reflects plant adaptations to phosphorus (P) deficiency. We hypothesized that changes in rice root morphology reflect P deficiency decrease after ferric iron (Fe(III))-bound phosphate (Fe–P) dissolution in low-redox paddy soils. We developed a novel in-situ 32 P phosphor-imaging approach under flooding to estimate P uptake by rice roots released from Fe–P dissolution. 32 P-labeled ferrihydrite (31 mg P kg −1 ) was supplied either (1) in polyamide mesh bags (30 μm mesh size) to prevent roots but not microorganisms from direct Fe–P mobilization, or (2) directly mixed with soil to enable roots and microorganisms unrestricted access to the Fe–P. The establishment of low redox conditions (Eh values between −176 and −224 mV) drove the reductive dissolution of Fe–P. Rice root-derived organic acids alone were unable to control Fe–P dissolution, and Fe(III) reduction is predominately a microbially-mediated process. Direct root access to Fe–P raised both the number and mean diameter of crown roots and root tips, and increased P uptake by 149–231%. Crown root elongation rate, 32 P activities along roots and root tips were 5–133% higher when roots directly accessed Fe–P compared to Fe–P excluded from roots in mesh bags. Iron accumulation on roots depended on the rice growth stage, but not on their access to Fe–P. Roots' access to Fe–P increased rice crown roots elongation and branching and increased P accessibility under P deficiency. Graphical abstract: Image 1 Highlights: Fe–P dissolution increased rice root growth and induced root morphological changes. Increased root tip numbers raised P uptake by roots from the soil. Organic acids exuded by rice roots were unable to control Fe–P dissolution. Iron accumulation on root surface was independent of root's access to Fe–P.